2018
DOI: 10.3390/cryst8100376
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on the Spin-Transition in a Series of Fe(II) Dinuclear Triple Helicate Compounds

Abstract: This work explores the effect of lattice solvent on the observed solid-state spin-transition of a previously reported dinuclear Fe(II) triple helicate series 1–3 of the general form [FeII2L3](BF4)4(CH3CN)n, where L is the Schiff base condensation product of imidazole-4-carbaldehyde with 4,4-diaminodiphenylmethane (L1), 4,4′-diaminodiphenyl sulfide (L2) and 4,4′-diaminodiphenyl ether (L3) respectively, and 1 is the complex when L = L1, 2 when L = L2 and 3 when L = L3 (Craze, A.R.; Sciortino, N.F.; Bhadbhade, M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 70 publications
3
7
0
Order By: Relevance
“…Similarly, the χ m T product plateaus until 25 K, where it drops sharply again due to zero-field splitting. Previous studies performed on analogous helicate compounds demonstrated a similar trend both before and after extended heating at high temperatures, exhibiting a one-step profile before the high-temperature isotherm and a two-step transition afterward. , Furthermore, in comparison to the PF 6 – , BF4 4 – , and ClO 4 – salts of 1 previously reported by Tuna et al, the spin transition of 1 (an I – salt) was similar in nature to that of the ClO 4 – salt, while that of the PF 6 – salt was similar to that of 3 .…”
Section: Resultssupporting
confidence: 74%
“…Similarly, the χ m T product plateaus until 25 K, where it drops sharply again due to zero-field splitting. Previous studies performed on analogous helicate compounds demonstrated a similar trend both before and after extended heating at high temperatures, exhibiting a one-step profile before the high-temperature isotherm and a two-step transition afterward. , Furthermore, in comparison to the PF 6 – , BF4 4 – , and ClO 4 – salts of 1 previously reported by Tuna et al, the spin transition of 1 (an I – salt) was similar in nature to that of the ClO 4 – salt, while that of the PF 6 – salt was similar to that of 3 .…”
Section: Resultssupporting
confidence: 74%
“…Here, we will attempt to correlate the observed solid-state VT behavior of dinuclear cobalt bis­(dioxolene) complexes with the solution-state electrochemistry. This comparison neglects the effects of packing in the solid-state, which are important for dinuclear SCO complexes, as well as the effects of solvent and electrolyte on electrochemistry, so we compare values recorded in MeCN with Bu 4 NPF 6 where possible . The evaluation is supported by the excellent agreement of gas phase DFT predictions and solid-state magnetic data as well as the observation of similar two-step VT interconversions for solid 1a and 1b and for 1b in solution …”
Section: Discussionmentioning
confidence: 82%
“…Multistep transitions of molecular origin may be accessed with molecules on surfaces, in solution or as noncrystalline materials, and are therefore more versatile than traditional multistep switchable materials that depend on crystallographically unique complexes or interactions in extended solids. ,, A simple example of a two-step interconversion in a molecular species is a dinuclear metal complex that exhibits spin crossover (SCO) at each of the metal centers . The origin of the two-step SCO transitions observed for some dinuclear Fe­(II) complexes has been investigated extensively and has been linked to the use of constrained ligands to increase electronic communication, intermolecular interactions, and the stability of the mixed low spin-high spin state . The current understanding is that small changes in one metal site, upon SCO at the other site, are insufficient to give rise to the two-step interconversion, , and instead the transition profile is directed by local electronic effects, which are difficult to control …”
Section: Introductionmentioning
confidence: 99%
“…To sum it all up, these results demonstrate that the irreversible spin conversion at around 400 K in the first heating process is related to the crystal-to-amorphous transformation associated with the loss of lattice MeCN solvent. Desolvation effects are reported in a variety of SCO systems in both positive (occurrence of abrupt and/or hysteretic spin transition) and negative (disappearance of SCO) ways [78][79][80][81][82][83][84] but a concomitant crystal-to-amorphous transformation is rarely observed [85]. Temperature dependence of the χMT product for 1 at a sweep rate of 2 K min −1 .…”
Section: Magnetic Propertiesmentioning
confidence: 99%